2019
DOI: 10.1186/s12864-019-5714-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis of trout skin pigment cells

Abstract: Background Enormous variability in skin colour and patterning is a characteristic of teleost fish, including Salmonidae fishes, which present themselves as a suitable model for studying mechanisms of pigment patterning. In order to screen for candidate genes potentially involved in the specific skin pigment pattern in marble trout (labyrinthine skin pattern) and brown trout (spotted skin pattern), we conducted comparative transcriptome analysis between differently pigmented dermis sections of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 69 publications
2
42
0
Order By: Relevance
“…This information allowed for the detection of CPLs associated to candidate genes formerly identified in former pigmentation studies. These CPLs complement gene expression studies by Sivka et al (2013) and Djurdjevič et al (2019) and improve knowledge on the genomic basis of pigmentation in the brown trout. While pigmentation patterns are important to evaluate the impact of hatchery individuals into wild trout populations (Mezzera et al, 1997; Aparicio et al, 2005), we showed that it is premature to rely on phenotypic colour patterns as a proxy of genome-wide admixture to promote management decisions.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This information allowed for the detection of CPLs associated to candidate genes formerly identified in former pigmentation studies. These CPLs complement gene expression studies by Sivka et al (2013) and Djurdjevič et al (2019) and improve knowledge on the genomic basis of pigmentation in the brown trout. While pigmentation patterns are important to evaluate the impact of hatchery individuals into wild trout populations (Mezzera et al, 1997; Aparicio et al, 2005), we showed that it is premature to rely on phenotypic colour patterns as a proxy of genome-wide admixture to promote management decisions.…”
Section: Discussionmentioning
confidence: 78%
“…The RAD-locus detected by both RDA and single-trait GWAS for black spotting is located ∼21kb downstream of GJD2 (Gap-junction protein Δ2 gene; located on LG9 of S. trutta ; Table S4). This gene was found differentially expressed in trout skin (marble vs fario/Atlantic morph) by Djurdjevič et al (2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the color pattern variability of skin pigment of the trout, the expression of MITF decreased to a greater extent in the light region than in the black spot, which is a similar pattern MITFA showed in the A. baenschi. However, MITFB showed a different expression pattern in the same species (Djurdjevič et al, 2019). MITF found in the chicken did not show any significant differential expression patterns between the white type and the black type (Zhang J. et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In order to further analyze the DEGs of two distinct color morphs of C. argus, we screened the number of DEGs using the AT1-3 as a control group. In previous studies, a large number of DEGs were found in black and light skin of freshwater sticklebacks (Greenwood et al, 2012); and a total of 244 DEGs (177 up-and 67 down-regulated) were found in normal and albino Triplophysa rosa (Xiao, 2017); and over 3000 DEGs were obtained in three phenotypic Pristella maxillaris (Bian, 2019), and 18,087, 61,751, and 87,737 DEGs between marble and brown trout were grouped by using GO analysis (Djurdjevič et al, 2019). In this study, a total of 1024 DEGs were found, including 559 up-and 465 down-regulated.…”
Section: Analysis Of Differentially Expressed Genesmentioning
confidence: 99%